2013
DOI: 10.1093/mnras/stt1849
|View full text |Cite
|
Sign up to set email alerts
|

The link between magnetic fields and filamentary clouds: bimodal cloud orientations in the Gould Belt

Abstract: The orientations of filamentary molecular clouds in the Gould Belt and their local ICM (inter-cloud media) magnetic fields are studied using near-infrared dust extinction maps and optical stellar polarimetry data. These filamentary clouds are a few-to-ten parsecs in length, and we find that their orientations tend to be either parallel or perpendicular to the mean field directions of the local ICM. This bimodal distribution is not found in cloud simulations with super-Alfvénic turbulence, in which the cloud or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
161
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(181 citation statements)
references
References 74 publications
19
161
1
Order By: Relevance
“…Such alignment of strong magnetic field models and misalignment of weak magnetic field models are also presented in the simulations not including turbulence (Van Loo et al 2014). In observations, the correlation between the orientations of clouds and magnetic fields is found to be either-parallelor-perpendicular in filamentary clouds from few to tens pc scales (Li et al 2013;Planck Collaboration et al 2016) and in massive cores at 0.1-0.01 pc scales Koch et al 2014), suggesting a dynamically important role of magnetic fields in various physical scales (see Li et al 2014 for a review).…”
Section: Introductionsupporting
confidence: 55%
“…Such alignment of strong magnetic field models and misalignment of weak magnetic field models are also presented in the simulations not including turbulence (Van Loo et al 2014). In observations, the correlation between the orientations of clouds and magnetic fields is found to be either-parallelor-perpendicular in filamentary clouds from few to tens pc scales (Li et al 2013;Planck Collaboration et al 2016) and in massive cores at 0.1-0.01 pc scales Koch et al 2014), suggesting a dynamically important role of magnetic fields in various physical scales (see Li et al 2014 for a review).…”
Section: Introductionsupporting
confidence: 55%
“…Furthermore, Fiege & Pudritz (2000) showed that also a toroidal magnetic field could stabilize the filament against radial collapse. However, observations show that the magnetic field in filaments seems to be preferentially perpendicular to the major axis (Chapman et al 2011;Sugitani et al 2011;Planck Collaboration et al 2014a) although also parallel configurations are observed (Li et al 2013;Pillai et al 2015;Planck Collaboration et al 2014b). Under the assumption that there is indeed a universal width for star forming filaments of the order of 0.1 pc as proposed by André et al (2014) (or even larger, see Schisano et al 2014), our results raise the question what mechanism allows to retain this width.…”
Section: A Universal Filament Width?mentioning
confidence: 99%
“…According to Arzoumanian et al (2011), this can be converted into central column densities Observations show that filaments are most likely magnetized with a direction of the magnetic field which is either perpendicular to the major axis 2 of the filament (e.g. Chapman et al 2011;Sugitani et al 2011;Planck Collaboration et al 2014a) or parallel to it (Li et al 2013;Pillai et al 2015;Planck Collaboration et al 2014b). The preferred direction of the magnetic field in the densest parts, however, is still not entirely certain: Dust polarisation maps usually reveal a strong decrease of the polarisation towards the densest regions, which leads to some uncertainty about the field direction within the filament (e.g.…”
Section: Initial Conditionsmentioning
confidence: 99%
“…numerical simulation by Vestuto et al 2003;Li et al 2008). Li et al (2013) examined the orientation of the filamentary giant molecular clouds of the Gould Belt (NH ≈ 2 × 10 21 -2 × 10 22 cm −2 ) relative to the magnetic fields of the intercloud medium (ICM) and found a bimodal distribution. Most clouds are oriented either perpendicular or parallel to ICM B-fields, with offsets typically less than 20 degrees.…”
Section: Introductionmentioning
confidence: 99%
“…We have examined scales on the order of a few parsec, smaller than the Gould Belt clouds examined in Li et al (2013), but on the same physical scales as the Serpens South cloud (e.g. Sugitani et al 2011;Kirk et al 2013) and the Taurus B211 filament (Palmeirim et al 2013).…”
Section: Introductionmentioning
confidence: 99%